Understanding Phenomena of Thin Silicon Film Crystallization on Aluminium Substrates. (December 2015) - Bellanger, Pierre; Maurice, Claire; Minj, Albert; Roques, Stephane; Bjørge, Ruben; Lunder, Otto; Ulyashin, Alexander; Slaoui, Abdelilah
Abstract: The realization of crystalline silicon thin films on foreign substrates is an attractive alternative to the ingot casting aiming at a reduction in total costs. The purpose of this work is to form polycrystalline silicon films using the crystallization of amorphous silicon deposited on aluminum (Al) substrates. The Al-substrate is used as a catalyzer for silicon crystallization but also as a conductive substrate and as a back reflector for the photovoltaic cell. The crystallization of 1-5 μm thick amorphous silicon films were carried out at a temperature of 550 °C and for duration times from 10 to 80 min. The crystallized silicon films were then characterized by Raman spectroscopy, scanning electron microscopy and by electron backscatter diffraction. The analysis show that the annealed layer is composed of two distinct layers: a thin polysilicon film located just above the Al substrate and on the top a thicker layer made of a mix of silicon and aluminum. The thickness of the polysilicon film is found to increase with the annealing time. The crystallization of 5 μm thick amorphous silicon during 80 min resulted in a 1 μm thick polysilicon layer composed of grains of few micrometers in size. The mechanisms of accelerated crystallization are discussed. Such polysilicon films can be used as a seed layer for the growth of a thicker absorbing silicon film for photovoltaic applications.